Effects of Petrol Exposure on Glucose, Liver and Muscle glycogen levels in the Common African toad Bufo regularis (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study investigated the effects of exposure to petrol on blood glucose, liver and muscle glycogen levels in the common African toad Bufo regularis. A total of 126 adult toads of either sex weighing between 70-100g were used for this study. The experiment was divided into three phases. The phase 1 experiment the acute toxicity test consisted of animals divided into six groups of 10 toads per group and were exposed to water (H2O), H2O + Tween 80, 2ml/l, 3ml/l, 5ml/l, and 10ml/l of petrol respectively for 96 hours using the static renewal bioassay system. In the Phase 2 experiment, the animals were exposed to H2O, H2O + Tween 80, 0.14ml/l, 0.3ml/l, 0.6ml/l, and 1.13ml/l of petrol respectively for 3 days; while in phase 3 experiment they were exposed to petrol solutions for 14 days. After the various exposures, the blood glucose, liver and muscle glycogen contents were determined using standard methods. The results of the study showed that the median lethal concentration of petrol (96 hours LC50) was 4.5ml/l and sub-lethal concentration of petrol caused mortality of animals. Exposure to petrol solutions for 3 days had no significant effect on blood glucose level of the animals but caused significant decrease in the liver and muscle glycogen levels at high concentrations. In the animals exposed to petrol solutions for 14 days, there was a significant increase in glucose levels and significant reduction in liver and muscle glycogen levels at high concentrations when compared with the control. The results show that sub-lethal concentrations of petrol can cause mortality of animals, hyperglycemia and reduction in liver and muscle glycogen levels. The effects of petrol exposure on carbohydrate metabolism depend on the concentration and duration of exposure.
Keywords: Petrol; Blood glucose; Liver glycogen; Muscle glycogen